Synthesis and Characterization of Some Useful Thermoelectric Materials - Singh, Jaspal; Verma, S.S. (Asian Journal of Chemistry, 2019)
This paper aims to introduce the synthesis and characterization of some useful thermo electric pellets in order to determine their ability to convert waste heat into electricity. The thermo electric pellets of Bi2Pb3, Bi2Te3 and Pb2Te3 in cylindrical dimensions are prepared by 15 mm mixture of different compositions. The research work explores the facts that how such kind of the semiconducting materials can be utilized as thermo-electric power generation elements. The performance of these pellets analyzed not only in the normal mode but also under the effect of electric and magnetic fields, which can exist already or applied in the condition of their operation. Thermo-emf generation is carried out in the normal mode and under the influence of applied electric and magnetic fields of different magnitudes in the temperature range of 190 °C. Hence, the paper is an outlet of the waste heat utilization with the influence of electric or magnetic field towards their conversion of waste heat into electricity by special sized thermoelectric pellets and the suitable chemical method of their preparation.